Psychological Flexibility Research Trends - Alrefi, Alrefi (Departemen Psikologi Pendidikan dan Bimbingan FIP Universitas Pendidikan Indonesia, 2019)
This research was aimed to see the research trend psychological flexibility last ten years. The literature review investigated research trend published in international journals, method in research problems, research method, and result of the research. Therefore, the researcher hope this research can contribute positively to the development of guidance and counseling faculty and can be one of the research development sources in the implementation of guidance and counseling services.